Mesucalophylloidin, a new isoprenylated 4-phenylcoumarin from Mesua calophylloides (Ridl.) Kosterm - Mulyadi Tanjung (Taylor & Francis Online, 2018)
A new isoprenylated 4-phenylcoumarin derivative, mesucalophylloidin (1) along with three known compounds, mammea A/BA cyclo F (2), calolongic acid (3) and isocalolongic acid (4) were isolated from the stem bark of Mesua calophylloides (Ridl.) Kosterm. Structures of all the compounds were elucidated using extensive spectroscopic methods, including UV, IR, HRESIMS, 1D and 2D NMR. Compounds 1–4 were evaluated for their cytotoxicity against P-388 cells, showing that compound 1 gave moderate activity with IC 50 6.26 μg/mL.